Analisis Penerapan Manajemen Operasional dalam Pendidikan Islam - Dwi Setiawati (Jurnal Publikasi Ilmu Manajemen, 2024)
Education is a barometer for the progress of a nation and the progress of a country or nation lies in its education. Managing Islamic educational institutions requires not only high professionalism, but also a mission of pure intention and strong mentality. Management of Islamic educational institutions requires two integrated aspects, namely the unification of the attitudes of managers and leaders who are characteristic of Islam. This study uses a type of library research or commonly called Library research, where the data in this study comes from various literatures, both physical data (books, magazines, newspapers, etc.) or online media. The research data obtained in this study were then studied using a theoretical and philosophical approach. According to Husaini Usman, the word management comes from Latin, namely the word manus which means hand and agere which means to do, the words are combined into the verb manager which means to handle and manager is translated into English in the form of the verb to manage which means to take care of, with the nouns management and manager for people who carry out management activities. Models that can be applied in Islamic education, namely: 1. Traditional Model 2. Participatory Model 3. Transformational Model 4. Islamic Value-Based Model 5. Islamic Financial Model 6. Empowerment Model 7. Technology and Innovation Model 8. Sustainable Model Suggestions for further research, to add operational management to education costs in Islamic education.